2013
DOI: 10.2478/bog-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Intra-annual climate variability and malaria transmission in Nigeria

Abstract: This study develops an integrated innovation for malaria early warning systems (MEWS), based on vulnerability monitoring, seasonal climate variability data, and epidemiologic surveillance. The main aim of the study is to examine the relationship between intra-annual climate variability and malaria transmission in Nigeria. For this study, climatic conditions considered suitable for the development of the malaria parasite and its transmission through the mosquito stage of its life cycle are temperatures within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
(2 reference statements)
0
16
0
Order By: Relevance
“…Some authors have reported strong correlation between high malaria prevalence and low levels of education; for instance a population that is well informed about the use of long lasting Insecticidal Nets (LLIN), indoor residual spraying (IRS) and intermittent preventive treatment of malaria in pregnancy (IPTp) could help reduce the prevalence of the disease [20,22]. South-West Nigerian communities have the highest malaria prevalence and transmission because rainfall is all year round with appropriate climatic conditions for vector breeding [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported strong correlation between high malaria prevalence and low levels of education; for instance a population that is well informed about the use of long lasting Insecticidal Nets (LLIN), indoor residual spraying (IRS) and intermittent preventive treatment of malaria in pregnancy (IPTp) could help reduce the prevalence of the disease [20,22]. South-West Nigerian communities have the highest malaria prevalence and transmission because rainfall is all year round with appropriate climatic conditions for vector breeding [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…These results are a reflection of the predicted probability of malaria, which is much more during the wet season, but the predicted probability of meningitis is much more during the dry season, especially in the Sahel and Sudan ecological zones (Table 4). Some studies have reported that malaria transmission was highly seasonal due to climatic conditions; these occurrences are much more frequent in recent times due to climate change (Asadullah et al ., 2008; Samdi et al ., 2012; Ayanlade et al ., 2013; Maggioni et al ., 2016; Nandargi, 2016; Guofeng et al ., 2017; Sergi et al ., 2019). Meningitis is predominant during the dry season.…”
Section: Influence Of Climatic Indices On Malaria and Meningitis Distmentioning
confidence: 99%
“…The dominant winds during the short period of dry season (Harmattan season) are the dry dusty northeasterly trade winds from the desert also called the tropical continental air mass (cT) which find their way to the South from the North (Eludoyin & Adelekan 2013). Annual rainfall total ranges from 1500 to 3000 mm over most of the South but can reach about 4000 mm over the southeastern part where rainfall is highest (Ayanlade et al 2013…”
Section: Climatology and Sources Of Subseasonal Predictability In Thementioning
confidence: 99%